Efectividad, rendimiento y desempeño del Sistema de Pensiones de México: estudio comparativo de las empresas oferentes (AFORE) - Fajer Herrera, Miguel (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
As all pension systems, the one established in 1917 in Mexico, has difficulties due the socio-economic variables changes, affecting them: increase in life expectation, workers‟ wages, permanency in jobs, life cost annuity insurance and survival, yields obtained by AFORES in pension funds investment, etc. The lost variable importance, resides in a worker accumulative resources, because it means growing pension amount that will be received at the end of his labor life. In a global economy, the taken decisions thousands of kilometers far produce certain effects in economic system, and therefore, on pension investment funds, causing workers assets value variations administered by AFORES. When uncertainty financial phenomena in markets appear as the initiated in 2007 in the American Union and that in 2010 it still persists, it produces on pensions systems certain affects, known as “minusvalía”. Additionally, affects registration process and AFORE workers' transfer, because it is provided information to the worker in thirty six months periods, to make a decision. It shows AFORE positions from better to worst, the change are according to base calculation applied. A thirty six months data vision is very different from twelve months one, the same as some as, benefits obtained. The decision only takes historical information in periods of thirty six months, and it doesn't reflect what is really happening in the short time. Based on described conditions, a worker would obtain bigger benefits if statistical information of twelve months, improving his vision and allowing him to make better decisions, reducing with it,

Como todo sistema de pensiones, el instaurado en México en 1997, presenta dificultades debido a los cambios en las variables socio-económicas como: el aumento en la expectativa de vida, el salario que percibe el trabajador, su permanencia en el puesto de trabajo, el costo de los seguros de renta vitalicia, los rendimientos obtenidos por la inversión de los fondos de pensión que realizan las AFORE, etc. La importancia de la última variable, radica en que mientras más recursos acumulados tenga el trabajador, mayor será el monto de la pensión que reciba al final de su vida laboral. Actualmente, para evaluar el desempeño de las SIEFORE, brazo ejecutor de las AFORE, en la inversión de los recursos pensionarios, se utiliza el Índice de Rendimiento Neto en períodos de 36 meses, comparando los resultados obtenidos por cada SIEFORE entre ellas mismas. El método de evaluación no es adecuado, ya que si todos los resultados fueran bajos simplemente se estaría determinando el menos malo. Al no existir en el sistema de pensiones, un parámetro de referencia contra el cual comparar y evaluar el desempeño de las AFORE, no será posible determinar si los rendimientos que obtienen las administradoras, cumplen realmente con el objetivo de preservar e incrementar los fondos de pensión de los trabajadores. La información en períodos de doce meses le daría al sistema, mayor transparencia al facilitar a través de índices objetivo, medir individualmente y en su conjunto la eficiencia y eficacia de los participantes en el sistema de pensiones. Mismos, que al presentar desviaciones alertarían sobre la necesidad de tomar medidas correctivas.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2010-0162; Salario; AFORE; Pensiones; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5952